REHABILITASI TUNA SOSIAL DI UNIT PELAKSANAAN TEKNIS DINAS (UPTD) RUMOH SEUJAHTERA BEUJROH MEUKARYA LADONG KABUPATEN ACEH BESAR - Hazimsyah, Mhd (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
Ninety-nine percent of children in LPKA are victims of lack of household harmony. The problem is that there are children who have been released and handed over to their parents, but return to the LPKA because they have repeated the same or different cases. This could also be because the family does not pay much attention during rehabilitation. This research aims to find out what factors cause drug abuse by children in andikpas at LPKA class II a Banda Aceh and what the impact of drug abuse by andikpas are after undergoing rehabilitation at LPKA class II a Banda Aceh. The method used is qualitative descriptive type. with data collection techniques carried out by observation, interviews and documentation. The results of the interview show that the factors that cause drug abuse by children in LPKA Class II A Banda Aceh are: 1) Self-caused due to the child's inability to adapt to the environment, unable to control themselves. 2) The causes originate from the family, such as a lack of harmony in the household so that the child has mental problems and seeks pleasure outside the home. 3) The availability of drugs itself. With the coaching program from LPKA class II Banda Aceh, these children can be more disciplined, more religious and more organized in carrying out their daily lives. Of course, this can remove their thoughts about their past actions that should not have happened.